If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3+-2u=-1
We move all terms to the left:
3+-2u-(-1)=0
We add all the numbers together, and all the variables
-2u+4=0
We move all terms containing u to the left, all other terms to the right
-2u=-4
u=-4/-2
u=+2
| 1=2h−1 | | -5=1−3c | | X(.0825)+x=41 | | 10=5−c | | 10=5−-c | | k/2+4=5 | | k/2+ 4= 5 | | 2f+1=11 | | -5(3-4x)=-175 | | -7(6x-4)=-266 | | 1+2j=3 | | 6(-5-7m)=306 | | 48/60=12/x | | 2/5(x)-3/5=1/3(x)+13/5 | | 6=2.7^4t | | 132=-3(7x-2) | | 32a^2=-8 | | -3x/4+1=-11 | | (4x+27)/2=(x+1)/3 | | 17,950=100+50w | | (x-2)/(-4)+2=5 | | 16/10000=n/3500 | | 1/10000=n/3500 | | 2(x+4)-1=5(x+2) | | 2(x+4)-1=2(x+11) | | 1/1000=x/3500 | | 3(x-1)+4=2(x+11) | | 29-3x=-9x | | 2(x-5)+1=25 | | 4x-3-x=3x-7 | | 2y-2=4y+3 | | 2-(3x+1)-(-x+4)=x+6 |